Indicadores de governança e resiliência socioecológica na perspectiva dos objetivos de desenvolvimento sustentável - Silva, Nicole Cavalcanti (2023)
The complexity and pressure for constant technical changes in the national and international governmental scene have driven public power, the private sector, organized civil society and academia to develop and adopt new environmental governance practices through the implementation of new technologies. , such as the development, implementation and analysis of indicators aimed at the most diverse contexts. In this sense, this study aims to develop a new conceptual, methodological and operational model with indicators of governance and socioecological resilience in the perspective of achieving the Sustainable Development Goals (SDGs), for municipal public management. To this end, the model took into account the integration, adaptation and consolidation of Hanai's (2009) models; the PCS (2017); and SEPLS (2013). In methodological terms, the research is exploratory, descriptive with a qualitative approach, conducted in the form of a case study, carried out through bibliographical and documentary research. As a suggestion for data analysis to consolidate the results, the analysis of the level of governance and socio-ecological resilience is indicated, through scores assigned to the indicators (indexes), as well as the percentiles of the dimensio ns and methodological triangulation. Thus, the scores for each indicator were transformed into indices ranging from 0 – 1 which, when aggregated, generated the indices of the dimensions and the general index of governance and socio-ecological resilience of the locus under study. For this purpose, the index construction method established by Ferreira et al. (2012). The main result of the research is the proposal of a new conceptual, methodological and operational model with sustainability indicators for assessing governance and socio-ecological resilience, for public authorities, private initiative, organized civil society and the tourist trade of communities. However, it is important to consider that there are not only Top-down strategies (those that only aim at the collaboration of technicians and public and private managers), but that they also include Bottom-up strategies that encompass and allow the participation of the community in the decision-making processes in favor of achieving the SDG targets.